Inshore cetaceans from the North and South Pacific coast of Costa Rica - Martínez-Fernández, Damián; Montero-Cordero, Andrea; May-Collado, Laura (Universidad Nacional, Costa Rica., 2010)
Inshore cetaceans from the North and South Pacific coast of Costa Rica. Twenty nine cetacean species occur in Costa Rican waters but extensive research has been conducted only for three species. The latter shows there is a lack of general and local information about these mammals, even when the country, has shown a remarkable growth in whale watching activities. The increasing use of marine resources in coastal areas has also developed the need to determine the occurrence of cetaceans in areas showing high tourist presence, in order to propose sound conservation measures. In this study, environmental variables were determined and subsequently related to the presence of the species recorded, out of 166 sightings, between 2005 and 2006. The species with highest proportion of sightings were Stenella attenuata (68%), followed by Megaptera novaeangliae (13%) and Tursiops truncatus (10%). The presence of spotted dolphins is related to changes in salinity and water transpar ency, while that of the humpback whale was related to wave height (Beaufort scale) and water temperature. The presence of seven species of cetaceans was confirmed in two coastal areas of the Pacific coast of Costa Rica, from which three are present throughout the year. Environmental variables were found related to the presence of at least two species. Rev. Biol. Trop. 59 (1): 283-290. Epub 2011 March 01 Universidad Nacional, Costa Rica. Instituto Internacional en Conservación y Manejo de Vida Silvestre